(untitled) (International Journal of Environmental Sciences, 2024)
Horticultural cultivation plays a crucial role in global food and nutrition security. This review explores recent advances and emerging trends in crop management, focusing on protected cultivation, precision agriculture, cultivar development, propagation innovations, micro-irrigation systems, nanotechnology applications, and integrated pest management. It highlights the potential of cutting-edge technologies like automation, robotics, artificial intelligence, and genetics to revolutionize horticulture. Key challenges such as sustainable intensification and the adaptation of plant systems to environmental changes are examined. The review emphasizes how the integration of advanced technologies and ecological approaches can lead to more productive, efficient, and climate-resilient horticultural systems. These innovations are essential for meeting the growing global demand for food while ensuring environmental sustainability.